Funktionsverbgefüge des Deutschen Untersuchungen zu einer Kategorie zwischen Lexikon und Grammatik - Harm, Volker (Reihe Germanistische Linguistik, 2021)
This study suggests a new definition of the highly disputed class of noun-verb combinations. The new approach offered here does not begin, as before, with the verb, but rather, examines the semantic and pragmatic properties of the noun-verb construction as a whole. Another important aim is to explain the status of noun-verb combinations in the transitional realm between lexicon and grammar, and between regularity and irregularity.